ADHESION AND PHAGOCYTOSIS PROPERTIES OFSTREPTOCOCCUS EQUI SUBSP. ZOOEPIDEMICUS ISOLATES FROM INDONESIA - Siti Isrina Oktavia Salasia (Jurnal Sain Veteriner, 1998)
An infectious diseases outbreak affecting pigs and monkeys in Bali in 1994, with case fatality rate (CFR) 75%. The disease widespread rapidly to the other district in Indonesia and developed serious problems. The causative agent involving the disease was Streptococcus equi subsp. zooepidemicus, a β-hemoIytic type of the streptococcus. The disease was consistently associated with meningitis, therefore the disease was named Streprococcal meningitis. The main aim of this study is todetect factors promoting the pathogenicity of the agent that could be showed by its characteristics and properties of the adhesions and phagocytosis. Eight and two isolates of Strepiacoccus equi subsp. zooepidemicus originated, from pigs and monkeys respectively were used in this study. The nature of bacterial surface proteins was characterized by hexadecane adherence test, hemaglutinating erythrocytes of various animals, adherence to epithelial cells and phagocytosis of the bacteria by polymorphonuclear leucocytes. The result of hexadecane adherence test showed that of the ten isolates oniy one culture of pigs isolates had a hydrophobic surface and the others were hedrophilic surface. The culture with hydrophobic surface agglutinated erythrocytes from chicken, rat and rabbit. This culture adhered in high numbers to epithelial cells and were more phagocytosed by polymorphonulear leucocytes. The cultures with hy drop hi lie surface showed no comparable reaction.